Assembly of a Highly Stable Luminescent Zn5 Cluster and Application to Bio‐Imaging. (16th August 2016) - Zeng, Ming‐Hua; Yin, Zheng; Liu, Ze‐Hui; Xu, Hai‐Bing; Feng, Ying‐Chun; Hu, Yue‐Qiao; Chang, Li‐Xian; Zhang, Yue‐Xing; Huang, Jin; Kurmoo, Mohamedally
Abstract: The assembly sequence of the coordination cluster [Zn5 (H2 L n )6 ](NO3 )4 ]⋅8 H2 O⋅2 CH3 OH (Zn5, H3 L n =(1, 2‐bis(benzo[d]imidazol‐2‐yl)‐ethenol) involves in situ dehydration of 1, 2‐bis(benzo[d]imidazol‐2‐yl)‐1, 2‐ethanediol (H4 L) through the formation of the [Zn(H3 L)2 ] + monomer, dimerization to [Zn2 (H3 L)2 ] +, dehydration of the ligand to [Zn2 (H2 L n )2 ] +, and the final formation of the pentanuclear cluster. The cluster has the following special characteristics: 1) high stability in both refluxing 37 % HCl and 27 % NH3, 2) low cytotoxicity, and 3) pH‐sensitive fluorescence in the visible‐to‐near‐infrared (Vis/NIR) region in the solid state and in solution. We have applied it as a fluorescent probe both in vivo and in vitro. Its H‐bonding ability is the key to its affinity and selectivity for imaging lysosomes in HeLa cells and tumors in male BALB/C mice. It provides a new type of sensitive and biocompatible fluorescent probe for detecting small tumors (13.5 mm 3 ).